Negócio jurídico fundacional - Dias, Daniel Pires Novais (2012)
This dissertation aims to examine closely the business foundation, which is the legal business through which the process of creating a private foundation in Brazilian law begins. It is a insufficiently addressed subject by the Brazilian doctrine: specialized works on Private Foundations approach the subject only indirectly and in a superficial vision, which is, from a perspective centered on the artificial foundational person, which implies a vision without pretensions of unity and coherence over the foundational business. This fragmentation has as negative consequence, a partial view on the foundational phenomenon, with special reflections on the process of creating the foundation and that, in practice, has corresponded to a disregard of the value of the negotiating freedom of the settlor. In the analysis of the foundational business we start from its formation, nearing the end of its extinction and juristic nature. The methodology used was the literature research of national and international authors and judicial decisions. Among the foreign authors, emphasis was placed on the German, Italian and Portuguese doctrines, because of the similarity of the theoretical bases and greater depth in which the subject is approached in these countries compared to the Brazilian law. The main problems faced are the interpretations of the requirement "free goods", contained in art. 62 of the Civil Code and also about the limit of the stipulation of the foundational purposes, predicted in the single paragraph of that article and, finally, the lawfulness of the reversal of the foundational residual patrimony in the event of termination of the foundation. The conclusions reached in each of these problems respectively were: the requirement free goods imposes that endowed goods to the foundation are not subject to the real rights of guaranty or under lien and its transmission is valid, the settlor can only create foundations for purposes of pursuing the collective interest, and, finally, the settlor may provide a reversal of patrimony that he himself transferred the property